Playing with Words: Motivating Young Learners to Construct Correct Sentences in English - García Hernández, Silvia (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2025)
this article shows how a group of students of english with difficulties with pro-ductive skills in terms of sentence order learnt how to produce correct senten ces. in order to solve their problem with sentence structure (and other questions derived from it such as demotivation and disruption), a game with different cards with which students could literally manipulate the language was designed. With the help of a motivating activity with different variations –from guided activities to more creative ones-, students learnt different strategies to apply when producing a message. By making them the protagonists of their own learning when playing this game, students moved from a more traditional metho-dology to a more engaging and significant one, becoming active and motivated learners who were finally able to construct correct sentences in english.